Surface Resistivity Correlation to Nano-Defects in Laser Powder Bed Fused Molybdenum (Mo)-Silicon Carbide (SiC) Alloys - Andrew Mason; Larry Burggraf; Ryan Kemnitz; Nate Ellsworth (Journal of Manufacturing and Materials Processing, 2025)
The integration of Silicon Carbide (SiC) nanoparticles into Laser Powder Bed Fusion (LB-PBF) Molybdenum (Mo) printing represents a significant advancement in refractory metal additive manufacturing. Our investigation examined how varying SiC nanoparticle sizes affect the microstructural and electrical properties of LB-PBF-printed molybdenum components while maintaining a 0.01 mass fraction of Mo. At an Linear Energy Densities (LED) of 1.8 J/mm, the addition of 80 nm SiC particles achieved a 46% reduction in porosity, while sheet resistance decreased by 6% at LED of 2.0 J/mm with 80 nm SiC particles. These performance improvements stem from several mechanisms: SiC particles serve as oxygen scavengers, facilitate secondary phase formation, and enhance laser absorption efficiency. Their dual role as sacrificial oxidizing agents and Mo disilicide phase promoters represents a novel approach to addressing microcracking and porosity in LB-PBF-printed Mo components. Through systematic investigation of particle size effects on both microscale and nanoscale properties, our findings suggest that optimized nanoparticle addition could become a universal strategy for enhancing LB-PBF processing of refractory metals, particularly in applications requiring enhanced mechanical and electrical performance.